2011
DOI: 10.1091/mbc.e11-02-0118
|View full text |Cite
|
Sign up to set email alerts
|

Golgi localization of ERManI defines spatial separation of the mammalian glycoprotein quality control system

Abstract: The current study provides mechanistic insight into the overlapping dynamics by which glycoprotein folding and quality control use distinct intracellular compartments as part of the proteostasis network in mammalian cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
55
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(64 citation statements)
references
References 55 publications
8
55
1
Order By: Relevance
“…An N594A mutation in COX-2 blocks enzyme degradation. During the process of distinguishing between terminally misfolded proteins and properly folded intermediates, ␣-mannosidases remove mannoses to trim the Asn-linked Man 9 -(GlcNAc) 2 oligosaccharides, generating an appropriate ERAD signal (38,43,44). Apparently, this occurs with the N-glycosyl moiety linked to Asn-594 of COX-2.…”
mentioning
confidence: 99%
“…An N594A mutation in COX-2 blocks enzyme degradation. During the process of distinguishing between terminally misfolded proteins and properly folded intermediates, ␣-mannosidases remove mannoses to trim the Asn-linked Man 9 -(GlcNAc) 2 oligosaccharides, generating an appropriate ERAD signal (38,43,44). Apparently, this occurs with the N-glycosyl moiety linked to Asn-594 of COX-2.…”
mentioning
confidence: 99%
“…Despite this traditional view, recent evidence from multiple investigators has begun to reevaluate how N-linked glycan processing contributes to mammalian ERAD (11,(23)(24)(25)(26)(27)(28). In support of this growing debate, we recently reported that MAN1B1 resides in the Golgi complex in numerous human cell lines rather than in the ER (29). Additional studies have begun to implicate its function as a possible cargo receptor based on its location, capacity to co-immunoprecipitate with the N-glycoprotein ERAD substrate Null Hong Kong (NHK), and the presence of ␥-COP binding motifs in its N-terminal cytoplasmic tail (30).…”
mentioning
confidence: 99%
“…This protein catalyzes the removal of the outermost mannose residue on the B-chain of high mannose N-linked glycoproteins generated in the ER (Gonzalez et al 1999). Although not noticed in our original resource, Pan et al (2011), showing a Golgi location with a monoclonal antibody to the protein, prompted reexamination of the resource. The assigned LC-MS/MS data clearly indicates a Golgi location.…”
Section: Expanding the Er -Golgi Axis Of Functional Interrelationshipmentioning
confidence: 96%
“…As with ERp44, the substrates of the enzyme (high-mannose linked N glycoproteins) are in the ER. A retrograde trafficking step to bring the enzyme to its substrate could assure that this mannosidase action is restricted to mature N-linked glycoproteins in the ER or for ERAD (Pan et al 2011), further extending the ER-Golgi axis of functional interrelationships.…”
Section: Expanding the Er -Golgi Axis Of Functional Interrelationshipmentioning
confidence: 99%